Influence Bulding Block Game On Social Emotional Behaviour - Inda, Jihan; Bachtiar, Muhammad Yusri; Rusmayadi, Rusmayadi (PINISI Discretion Review, 2024)
This study aims to determine the Effect of Building Block Games on the Social Emotional Behavior of Children Aged 4-5 Years at KB Raodhatut Thalibin, Lautang Village, Belawa District. Based on observations of the reality in the field, the problem is that children's social-emotional behavior is still low because building block game activities in play are still rarely carried out because children use slides, swings, climbing irons, and spider webs. The approach used is a quantitative approach with a Quasi-Experimental research type with a research design that is a nonequaivalent control group design. The population in this study were children aged 4-5 years in the Raodhatut Thalibin KB, Lautang Village, Belawa District. Sampling in this study was purposive sampling. The sample in this study were 12 children with 6 children as the experimental group and 6 children as the control group. The data collection technique used is descriptive statistical analysis and non-parametric statistical analysis. Based on the results of the study it can be concluded that the social emotional behavior of children who were treated with building block games in the experimental group was better than the control group. The results showed that building block game activities had a significant influence on the social-emotional behavior of children aged 4-5 years at the Raodhatut Thalibin KB, Lautang Village, Belawa District.